Long-term exposure to fine particulate matter constituents and metabolic syndrome, potential mediation by serum uric acid - Cai, Changwei; Chen, Yang; Feng, Chuanteng; Shao, Ying; Ye, Tingting; Yu, Bin; Jia, Peng; Yang, Shujuan (Environmental pollution (1987), 2023)
Exposure to fine particulate matter (PM₂.₅) was associated with the risk for metabolic syndrome (MetS) in the general population, but the contribution of individual PM₂.₅ constituent to this association and the potential pathway between PM₂.₅ constituents and MetS risk are not well elaborated. Thus, this investigation endeavors to explore associations between PM₂.₅ constituents and MetS in general populations, elucidating the relative importance of PM₂.₅ constituents and mediating effects of serum uric acid (SUA) on those associations. This study included 48,148 participants from a provincially representative cohort established in southwest China. The 3-year average concentrations of PM₂.₅ and its constituents (nitrate [NO₃⁻], sulfate [SO₄²⁻], ammonium [NH₄⁺], organic matter [OM], and black carbon [BC]) were estimated using a series of machine-learning models. Multivariate logistic regression and weighted quantile sum regression were used to estimate the independent and joint associations of PM₂.₅ constituents with MetS and their contribution to joint associations. Mediation analysis examined the potential mediation effects of SUA. Each interquartile range (IQR) increase in the concentration of PM₂.₅ constituents were all positively associated with the increased MetS odds, including SO₄²⁻ (OR = 1.15 [1.11, 1.19]]), NO₃⁻ (OR = 1.12 [1.08, 1.16]), NH₄⁺ (OR = 1.13 [1.09, 1.17]), OM (OR = 1.09 [1.06, 1.13]), and BC (OR = 1.09 [1.06, 1.13]). Their joint associations on MetS were mainly attributed to SO₄²⁻ (weight = 46.1%) and NH₄⁺ (44.0%). The associations of PM₂.₅ constituents with MetS components’ dysfunctions were mainly attributed to NH₄⁺ for elevated BP (51.6%) and reduced HDL-C (97.0%), SO₄²⁻ for elevated FG (68.9%), NO₃- for elevated TG (51.0%), and OM for elevated WC (63.0%). Percentages mediated by SUA for the associations between PM₂.₅, SO₄²⁻, NO₃⁻, and BC with MetS were 13.6%, 13.1%, 10.6%, and 11.1%, respectively. Long-term exposure to PM₂.₅ constituents, mainly NH₄⁺ and SO₄²⁻, was positively associated with MetS odds, partially mediated by SUA.